Occurrence of Nigrospora sphaerica causing leaf blight on Chrysanthemum morifolium in China. (July 2022) - Luo, Xiujun; Xi, Yue; Shen, Chenjia; Wang, Mingshuang; Wang, Huizhong
Abstract: Chrysanthemum ( Chrysanthemum morifolium ) is one of the most popular cut flowers as well as an important medicinal plant in China. In the summer of 2020, leaves of C. morifolium showing leaf blight widely occurred. As a result, C. morifolium 's quality and economic worth were both severely impacted by this disease. A fungal species was isolated from necrotic leaves. Its colony was whitish to gray and produces elliptical, dark conidia. To identify the pathogen, the internal transcribed spacer (ITS) region and translation elongation factor 1-alpha (TEF) gene were amplified and sequenced. Phylogenetic analyses confirmed that this pathogen is Nigrospora sphaerica . Virulence arrays were undertaken by inoculating healthy leaves with a mycelial plug of N. sphaerica . The fungus was re-isolated from the infected leaves, which is identical to the N. sphaerica that had been recovered from C. morifolium leaves previously. Taken together, N. sphaerica is the causal agent of leaf blight on C. morifolium . Highlights: Leaf blight disease appeared on leaves of Chrysanthemum morifolium in China. The pathogen was isolated and its morphology was characterized. ITS and TEF gene was used for identification of the fungal pathogen. Nigrospora sphaerica was first reported to cause leaf blight on C. morifolium in China.